Quantitative assessment of lung cancer associated with genes methylation in the peripheral blood. (1st May 2013) - Tan, Shanjuan; Sun, Changqing; Wei, Xiaoling; Li, Yanqiang; Wu, Yongjun; Yan, Zhen; Feng, Feifei; Wang, Jing; Wu, Yiming
ABSTRACT Background: Lung cancer is the leading cause of cancer-related deaths worldwide due mainly to late diagnosis and poor prognosis. Aberrant promoter methylation is an important mechanism for silencing of tumor suppressor genes during carcinogenesis and a promising tool for the development of molecular biomarkers. Methods: We evaluated the p16, RASSF1A, and FHIT genes promoter methylation status in peripheral blood DNA between 200 lung cancer patients and 200 normal controls by using SYBR green-based quantitative methylation-specific PCR (qMSP). Results: There were statistically significant differences in the methylation status of p16, RASSF1A, and FHIT between the cancer cases and controls (p16: P = .008, RASSF1A: P = .038, FHIT: P = .002). When the subjects were categorized into quartiles based on the genes methylation status, the risk of lung cancer was found to increase as methylation status increased (p16: Ptrend = .002, RASSF1A: Ptrend = .014, FHIT: Ptrend = .001). When the median of methylation status was used as the cutoff between high and low methylation status, individuals with high methylation status were at a significantly higher risk of lung cancer than those with low methylation status (p16: adjusted odds ratio = 1.597, P = .028; RASSF1A: adjusted odds ratio = 1.551, P = .039; FHIT: adjusted odds ratio = 1.763, P = .008). In addition, there were no significant correlations between p16, RASSF1A, or FHIT methylation status and gender (P > .05), age (P > .05), smoking history (P > .05), histological type (P > .05), or clinical stage (P > .05). Conclusions: These results suggest that the high methylation statuses of p16, RASSF1A, or FHIT genes were associated with a significantly increased risk of lung cancer; the risk of lung cancer increased as the methylation status increased. Further investigation of their definitive usefulness in clinical practice is warranted.